Analisis Model Cooperative Integrated Reading Composition dalam Meningkatkan Pemahaman Membaca Siswa Kelas 5 SD - Nuryani, Nuryani; Utami, Nidya Chandra Muji; Nurhasanah, Nina (Jayapangus Press, 2025)
This research is motivated by the low reading comprehension ability of students at Madrasah Ibtidaiyah Al-Muhajirien Jakapermai, which is caused by less effective conventional learning methods. The purpose of this study is to improve the reading comprehension ability of grade V students through the application of the Cooperative Integrated Reading and Composition (CIRC) model. The method used in this study is classroom action research (PTK) which is carried out in three cycles, where each cycle consists of planning, action, observation, and reflection. Data was collected through observation, student worksheets (LKS), and reading comprehension tests. The results show that the application of the CIRC model significantly improves students' reading comprehension skills. In the first cycle, the average score of students' reading comprehension was 67.27, with 70% of students achieving a score above the Minimum Completeness Criteria (KKM). In the second cycle, the average score increased to 77.76, with 80% of students achieving scores above the KKM. In the third cycle, the average score reached 83.2, and 90% of students successfully met the KKM. In addition, observations showed increased student engagement and motivation during the learning process, where students were more active in participating in group discussions and reading activities, as well as showing higher self-confidence. The conclusion of this study is that the CIRC model has proven to be effective in improving students' reading comprehension skills. The application of this model not only improves learning outcomes, but also encourages activeness, collaboration, and communication between students. Students show a greater interest in reading and are better able to understand the reading material. Therefore, it is recommended that teachers apply the CIRC model as an alternative in learning to read in the classroom, in order to improve the quality of education and overall student learning outcomes.